THE COMPETENCE AND PERFORMANCE OF VILLAGE APPARATUS IN SIDOARJO REGENCY - Totok Wahyu Abadi; Isnaini Rodiyah; Hendra Sukmana (Universitas Muhammadiyah Sidoarjo, 2020)
The village apparatus is a part of administrator of the village. They have an important role in realizing the progress of the nation through the village. This study described three competencies (basic, management, and technical) that were possessed by village apparatus, their performance, and the influence of these competencies towards performance of the village apparatus in providing village administrative services in Sidoarjo Regency. This quantitative research was conducted with the sample of 147 respondents from the village apparatus. Through simple random sampling technique, the data was collected by questionnaire distribution and interviews. After collecting and coding, the data were analyzed by frequency distribution and multiple linear regression based on SPSS 20. The results showed that basic competencies, management abilities, technical skills, and performance of village apparatus in Sidoarjo Regency were included poor category. Second, basic competencies, management abilities, and technical skills had an influence on the performance of village apparatus. The novelty of this research was that human resources who had good job competencies were able to show quality performance characteristics. The higher competency was possessed by an individual, the higher the quality of one's performance.